Model of competitive activity of highly qualified decathlers - Ogandjhanov, A. L.; Salamatov, M. B.; Tsyplenkova, E. S.; Loktionov, S. E. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to develop a model of competitive activity of highly qualified decathletes, to formulate a technology for managing the training process of track and field all-round athletes based on the model.